Combating Crime on the Dark Web Learn how to access the dark web safely and not fall victim to cybercrime - Nearchou, Nearchos; Nearchou, Nearchos (Packt Publishing, 2023)
Know your enemy and counter the dark web criminality with this easy-to-follow guide, including a detailed tour of the dark web ecosystem and the tools and tactics used to mitigate cyber threatsKey FeaturesGet up to speed with the ins and outs of cybercriminal activity on the dark webBecome familiar with the tools and techniques that are used to fight serious crimeGain a keen understanding of the crime ecosystem on the dark web and the best practices to keep it in checkBook DescriptionIn today's world, the crime-prevention landscape is impossible to navigate. The dark web means new frontiers of combat against bad actors that pop up daily. Everyone from narcotics dealers to human traffickers are exploiting the dark web to evade authorities. If you want to find your feet in this tricky terrain and fight crime on the dark web, take this comprehensive, easy-to-follow cyber security guide with you.Combating Crime on the Dark Web contains everything you need to be aware of when tackling the world of the dark web. Step by step, you'll gain acumen in the tactics that cybercriminals are adopting and be equipped with the arsenal of strategies that are available to you as a cybersecurity specialist.This cyber security book ensures that you are well acquainted with all the latest techniques to combat dark web criminality. After a primer on cybercrime and the history of the dark web, you'll dive right into the main domains of the dark web ecosystem, reaching a working understanding of how drug markets, child pornography, and human trafficking operate. Once well-versed with the functioning of criminal groups, you'll be briefed on the most effective tools and methods being employed by law enforcement, tech companies, and others to combat such crimes, developing both a toolkit and a mindset that can help you stay safe from such criminal activities and can be applied in any sector or domain. By the end of this book, you'll be well prepared to begin your pushback against the criminal elements of the dark web.What you will learnUnderstand the history of cybercrime, the dark web, and the use of TorDiscover the ecosystem of dark web drug marketsBecome familiar with the methods law enforcement use to stop child abusersDive deep into real-life human trafficking cases and how they were tackledExplore sting operations, honeypots, and cybercrime prevention methodologiesGain expertise in Pipl Search, MEMEX, BITCRIME, and other anti-crime toolsInvestigate open-source intelligence and intelligence-led policingSet up a framework for disrupting organized crime on the dark webWho this book is forThis book is for aspiring cybercrime investigators, cybersecurity enthusiasts, and anyone else who is interested in learning about this dark side of the internet. The book mainly focuses on preventing crimes on the dark web and is written in a simple way so that you can understand it with ease.